Synthesis of 3-Trifluoromethylbenzofurans via Palladium-Catalyzed Tandem Elimination/Annulation of β-Chloro-β-(trifluoromethyl)styrenes with 2-Halophenols - Wang, Chong; Chen, Lian-Hui; Deng, Chen-Liang; Zhang, Xing-Guo (Synthesis, 2014)
A palladium-catalyzed tandem elimination and annulation reaction has been developed. In this way, a variety of 3-trifluoromethybenzofurans were prepared in moderate to good yields via tandem reaction of β-chloro-β-(trifluoromethyl)styrenes with 2-iodophenols and 2-bromophenols.
Keywords: tandem reaction; trifluoromethyl; benzofuran; X-phos; palladium acetate; cesium carbonate